Microstructure and thermal stability of rf‐plasma‐nitridated α‐(AlGa)2O3 grown by mist CVD. Issue 8 (3rd July 2017) - Buma, A.; Masuda, N.; Araki, T.; Nanishi, Y.; Oda, M.; Hitora, T.
Abstract : A new lattice‐matching substrate material for the growth of AlGaN is proposed. This substrate is prepared by the rf‐radical beam‐based nitridation of α‐(AlGa)2 O3, which is grown by mist chemical vapor deposition (CVD). We consider the effect of the nitridation process using reflection high‐energy electron diffraction (RHEED), transmission electron microscopy (TEM), scanning transmission electron microscopy‐electron energy loss spectroscopy (STEM‐EELS) and X‐ray photoelectron spectroscopy (XPS). Surface of α‐(AlGa)2 O3 changed from corundum structure to wurtzite structure of AlGaN by nitridation using rf‐radical beam was observed. In addition, we discuss the thermal stability of α‐(AlGa)2 O3 . X‐ray diffraction ω–2θ profile to characterize the phase transition was performed.